Chemical Approaches to Dynamically Modulate the Properties of Synthetic Matrices. - LeValley, Paige J. (ACS Macro Lett, 2018)
As knowledge about the dynamic nature of tissues within the human body has increased, the need for cell culture models that mimic the properties of these dynamic microenvironments has grown. Hydrogels are useful platforms for investigating cellular responses to microenvironment cues in disease and regeneration processes and recently have been designed to contain dynamic bonds to regulate the mechanical and biochemical properties of the matrix in three-dimensional cell culture applications. In this Viewpoint, we highlight recent advances in developing hydrogels with dynamic properties for modeling aspects of human tissues, providing control over the properties of the synthetic matrix on multiple length and time scales, and their application for understanding or directing cell response. We conclude by discussing how orthogonal chemistries can be utilized to design dynamic hydrogel platforms for controlling both the mechanical and biochemical environment, affording opportunities to investigate more complex questions associated with disease progression and tissue regeneration.